1994
DOI: 10.1042/bj2990129
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the CysB protein of Klebsiella aerogenes: direct evidence that N-acetylserine rather than O-acetylserine serves as the inducer of the cysteine regulon

Abstract: The cysB gene of Klebsiella aerogenes has been cloned, sequenced and shown to complement the cysteine auxotrophic phenotype of Escherichia coli cysB mutants. The K. aerogenes cysB gene is predicted to encode a protein of 324 amino acid residues that shares approx. 95% sequence similarity with the Salmonella typhimurium and E. coli CysB proteins. Gel-retardation assays demonstrate that the purified protein binds to DNA fragments containing either the K. aerogenes cysb promoter or the S. typhimurium cysJIH promo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 30 publications
1
26
0
Order By: Relevance
“…The upstream cysB region contains a conserved TTATT sequence, situated 78 bp upstream from the cysB translational start codon, found in several cysB promoters and shown to bind the CysB protein in vitro (the TTATT sequence was not found in the CysB-binding site of palgD ). However, no other significant similarity could be found between the cysB promoter region and promoter sequences of several cysB genes (Kredich, 1992;Lynch et al, 1994).…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…The upstream cysB region contains a conserved TTATT sequence, situated 78 bp upstream from the cysB translational start codon, found in several cysB promoters and shown to bind the CysB protein in vitro (the TTATT sequence was not found in the CysB-binding site of palgD ). However, no other significant similarity could be found between the cysB promoter region and promoter sequences of several cysB genes (Kredich, 1992;Lynch et al, 1994).…”
Section: Discussionmentioning
confidence: 89%
“…Comparison of the cysB deduced amino acid sequence with sequences deposited in the Swiss-Prot Protein Data Bank revealed sequence similarities with a number of regulatory proteins of the LysR family. The highest homology scores included CysB proteins from E. coli and S. typhimurium (Ostrowski et al, 1987) and from Klebsiella aerogenes (Lynch et al, 1994); these proteins shared 64% identity, with no gap, with the P. aeruginosa protein. When only a part of the N-terminal region (amino acids (aa) 25-50) of CysB was used to search the database, several additional LysR family members, including OxyR (Christman et al, 1989), NAC (Schwacha and Bender, 1993), CynR (Sung and Fuchs, 1992), GltC (Bohannon and Sonensheim, 1989), TfdS (Kaphammer and Olsen, 1990), IlvY (Wek and Hatfield, 1986), and LysR (Stragier et al, 1983), showed significant similarities (data not shown).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The inability of cysE mutants to assimilate sulfide prevents methionine utilization via the proposed alternative pathway as well, resulting in complete lack of growth on methionine in liquid medium. The CysE protein produces O-acetyl-serine, both the substrate for sulfide assimilation and the effector for the CysB activator via its isomerization product N-acetyl-serine (15). Since MtcBC activity produces cysteine directly from homocysteine-without the use of a sulfide intermediate-we cannot attribute the lack of MtcBC action to a lack of sulfide incorporation.…”
Section: Discussionmentioning
confidence: 84%
“…3B). The CysB protein detects sulfur starvation as accumulation of o-acetylserine (via its isomer N-acetyl-serine [15]), the product of the CysE protein. In the screen detailed above, a cysE mutation prevented growth on methionine on solid and liquid media and caused cysteine auxotrophy even when transduced into an otherwise wild-type background.…”
Section: Resultsmentioning
confidence: 99%